2012
DOI: 10.1007/s10059-012-0048-8
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin Loop Formation in the β-Globin Locus and Its Role in Globin Gene Transcription

Abstract: Although linearly distant along mouse chromosome 7 and human chromosome 11, the mammalian β-globin gene is located in close proximity to the upstream locus control region enhancer when it is actively transcribed in the nuclear chromatin environment of erythroid cells. This organization is thought to generate a chromatin loop between the LCR, a powerful enhancer, and active globin genes by extruding intervening regions containing inactive genes. Loop formation in the β-globin locus requires erythroid specific t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 40 publications
1
37
1
Order By: Relevance
“…23,24 Further characterization of this region, by the use of transgenic animals, indicated that the LCR is absolutely required for high level of expression of the b-globin gene in erythroid cells. [25][26][27][28] The single genetic components of the LCR were identified as hypersensitive sites (HS) to the DNAse I in the chromatin of erythroid cells. 29 The chromatin at the individual HSs is composed of arrays of multiple ubiquitous and lineage-specific transcription factorbinding sites (discussed further below).…”
Section: Globin Synthesis Erythropoiesis and Iron Metabolism: A Compmentioning
confidence: 99%
“…23,24 Further characterization of this region, by the use of transgenic animals, indicated that the LCR is absolutely required for high level of expression of the b-globin gene in erythroid cells. [25][26][27][28] The single genetic components of the LCR were identified as hypersensitive sites (HS) to the DNAse I in the chromatin of erythroid cells. 29 The chromatin at the individual HSs is composed of arrays of multiple ubiquitous and lineage-specific transcription factorbinding sites (discussed further below).…”
Section: Globin Synthesis Erythropoiesis and Iron Metabolism: A Compmentioning
confidence: 99%
“…While other Hox-unrelated gene clusters are regulated coordinately (e.g., see Kim and Dean 2012), this precision in meta-cis regulation associated with temporal collinearity is thus far unique to Hox gene clusters. This time process requires a complete series of genes to be clustered, and hence the physical neighborhood of Hox genes at their genomic loci is a fundamental parameter to ensure a faithful anterior-to-posterior patterning in vertebrates.…”
Section: The Rationale Of Temporal Collinearitymentioning
confidence: 99%
“…The most prominent activity of LCRs is their strong transcription enhancing activity, as was studied in detail in case of the human developmentally regulated β-globin locus [51]. The functional role of LCRs became evident with studies in transgenic mice where it was determined that the LCR was responsible for developmental expression of the ɛ-globin genes [52,53]. LCRs are mostly located upstream of their target gene.…”
Section: Locus Control Regions (Lcrs)mentioning
confidence: 97%
“…The most widely accepted model of LCR action is the looping model [53,57]. According to this model the 5' hypersensitive site of the LCR forms a folded structure where the hypersensitive sites are in the core and act as docking site for the transcription factors.…”
Section: Locus Control Regions (Lcrs)mentioning
confidence: 99%